SARS-CoV-2 and the Immune Response in Pregnancy with Delta Variant Considerations - Patrida Rangchaikul; Vishwanath Venketaraman (MDPI AG, 2021)
As of September 2021, there has been a total of 123,633 confirmed cases of pregnant women with SARS-CoV-2 infection in the US according to the CDC, with maternal death being 2.85 times more likely, pre-eclampsia 1.33 times more likely, preterm birth 1.47 times more likely, still birth 2.84 times more likely, and NICU admission 4.89 times more likely when compared to pregnant women without COVID-19 infection. In our literature review, we have identified eight key changes in the immunological functioning of the pregnant body that may predispose the pregnant patient to both a greater susceptibility to SARS-CoV-2, as well as a more severe disease course. Factors that may impede immune clearance of SARS-CoV-2 include decreased levels of natural killer (NK) cells, Th1 CD4+ T cells, plasmacytoid dendritic cells (pDC), a decreased phagocytic index of neutrophil granulocytes and monocytes, as well as the immunomodulatory properties of progesterone, which is elevated in pregnancy. Factors that may exacerbate SARS-CoV-2 morbidity through hyperinflammatory states include increases in the complement system, which are linked to greater lung injury, as well as increases in TLR-1 and TLR-7, which are known to bind to the virus, leading to increased proinflammatory cytokines such as IL-6 and TNF-α, which are already elevated in normal pregnant physiology. Other considerations include an increase in angiotensin converting enzyme 2 (ACE2) in the maternal circulation, leading to increased viral binding on the host cell, as well as increased IL-6 and decreased regulatory T cells in pre-eclampsia. We also focus on how the Delta variant has had a concerning impact on SARS-CoV-2 cases in pregnancy, with an increased case volume and proportion of ICU admissions among the infected expecting mothers. We propose that the effects of the Delta variant are due to a combination of (1) the Delta variant itself being more transmissible, contagious, and efficient at infecting host cells, (2) initial evidence pointing to the Delta variant causing a significantly greater viral load that accumulates more rapidly in the respiratory system, (3) the pregnancy state being more susceptible to SARS-CoV-2 infection, as discussed in-depth, and (4) the lower rates of vaccination in pregnant women compared to the general population. In the face of continually evolving strains and the relatively low awareness of COVID-19 vaccination for pregnant women, it is imperative that we continue to push for global vaccine equity.